Pelatihan pola pengasuhan menghadapi anak trauma - Alfiandy Warih Handoyo (Riau Journal of Empowerment, 2020)
Sleman district has the high-risk potential of the natural disaster. Disaster risk has positive correlate to potential trauma risk, especially on children. Trauma will be rise direct after a disaster or delay or called posttraumatic stress disorder (PTSD). Parents are the most influential party to the child's development, so parents in disaster-prone areas must have the skills to deal with a traumatized child. The handling of trauma given to victims of natural disasters in Sleman Regency is only based on direct handling post-disaster. There is no advisory service for parents in dealing with traumatized children. Training needs to be given to parents, especially residents in locations that have a high potential for natural disasters. The training aims to provide readiness for parents to accompany traumatized children so that the impact of the trauma does not get worse. Based on the results of the application, it is proven that parents can perform parenting skills to assist traumatized children.